Pendidikan Moral Berbasis pada Karakteristik Siswa dan Budaya - -, Sutoyo (Joglo, 2011)
ABSTRACTThe booming at moral issues among teenagers, especially about drug abuse, teenage delinguncy, pornograph has aroused a hyphotesis that those are due to the failure at moral education.The are number at factors that influences a teenagers moral, namely his character and cultural exposure. Therefore, one at moral education becomes a strategic means to introduce and educated them about moral through various sectors, both formal and non formal educationIt is important to consider the characters and culture to implement moral educationKeywords : Moral Education, Characteristic, and culture